The winners seminar a leadership experience for youth - Harder, Carole; Carole Harder & Co.. (S.l.) ([New York, N.Y.] : Phoenix Films, 1900)
We always move in the direction of our current dominant thoughts. Since most of our fears are based on dark imaginings that have no real basis, it is vital for us to concentrate on desired results, instead of fears that suppress them.
Keywords: Motivation (Psychology); Thought and thinking